Design of a UWB circularly-polarized planar monopole antenna using characteristic mode analysis - Hyuk Heo; Myeong-Jun Kang; Seoungyong Park; Jisu Lee; Longyue Qu; Kyung-Young Jung (Scientific Reports)
Abstract This study presents a circularly-polarized (CP) planar monopole antenna designed for ultra-wideband (UWB) applications using characteristic mode analysis (CMA). Initially, a planar monopole antenna with a crescent moon-shaped radiator and a circular open-loop on an FR-4 substrate was designed to achieve wideband characteristics, however, this antenna only satisfied a 3 dB axial ratio (AR) bandwidth within the 8.78–9.4 GHz range. To enhance the AR bandwidth, a triangular slit, a shark fin-shaped stub, and an L-shaped strip were added to the ground plane, generating orthogonal modes in the desired frequency band using CMA. The overall dimensions of the proposed antenna are 30 × 24 × 1.6 mm2 (0.58 × 0.46 × 0.031 λ₀2). The − 10 dB S11 bandwidth is 5.73–10.78 GHz (61.21%) and the 3 dB AR bandwidth is 6–11.12 GHz (59.81%), achieving overlapped bandwidth from 6 to 10.78 GHz (56.9%). The proposed antenna has a realized gain 2.4–5.4 dBi and an average efficiency of 80% within the target frequency. A time-domain analysis, including group delay and system fidelity factor, is conducted to evaluate performance. The fabricated antenna demonstrates omnidirectional radiation patterns at various frequencies and performs well in both the time and frequency domains.